2015
DOI: 10.1111/1750-3841.13003
|View full text |Cite
|
Sign up to set email alerts
|

Salmon Protamine Decreases Serum and Liver Lipid Contents by Inhibiting Lipid Absorption in an In Vitro Gastrointestinal Digestion Model and in Rats

Abstract: Protamine has been used as an antiheparin drug and a natural preservative in various food products. However, limited studies have evaluated the physicochemical and functional properties of protamine. Hence, we assessed the mechanisms underlying the inhibition of lipid absorption following salmon protamine intake in in vitro and in vivo studies. In initial experiments, a salmon protamine hydrolyzate (PH) was prepared using in vitro simulated gastrointestinal digestion suppressed pancreatic lipase activity and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The fecal excretion of cholesterol was significantly higher in the protamine or RPR groups than in the control group, and fecal bile acid excretion significantly increased in the protamine and RPR-treated animals when compared with the controls ( Figure 5 c). These findings suggest that the hypocholesterolemic action of RPR or protamine is related to the inhibition of intestinal cholesterol absorption and was measured by the increase in fecal steroid excretion, similar to previous findings [ 14 , 19 ]. Regarding cholesterol metabolism, we evaluated the mRNA levels of SREBP2, HMGCR, and LDLR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fecal excretion of cholesterol was significantly higher in the protamine or RPR groups than in the control group, and fecal bile acid excretion significantly increased in the protamine and RPR-treated animals when compared with the controls ( Figure 5 c). These findings suggest that the hypocholesterolemic action of RPR or protamine is related to the inhibition of intestinal cholesterol absorption and was measured by the increase in fecal steroid excretion, similar to previous findings [ 14 , 19 ]. Regarding cholesterol metabolism, we evaluated the mRNA levels of SREBP2, HMGCR, and LDLR.…”
Section: Discussionsupporting
confidence: 91%
“…These effects show that protamine is a strong candidate for inhibiting lipid adsorption [ 11 , 12 ]. Protamine exhibits both hypocholesterolemic and anti-obesity effects in rats fed a HFD [ 13 , 14 , 15 ]. However, the active peptide and molecular mechanism of protamine鈥檚 anti-obesity and hypocholesterolemic actions have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…and liver cholesterol contents, whereas the diet containing 11.8 g/kg PG decreased serum TAG and liver cholesterol contents. Previous studies reported that diets containing 200 g/kg soybean 尾-conglycinin (29), 50 g/kg salmon protamine (30), and 40 g/kg sericin (31) reduced the lipid content in the serum and liver compared with a 200 g/kg casein diet. In the present study, decreased serum and liver lipid contents were produced with 12.5 g/kg PH or 11.8 g/kg PG diets, which is lower than in other studies.…”
Section: )mentioning
confidence: 99%
“…Highly nutritious lean fish protein is abundantly present in fish and consumed worldwide including in processed foods such as artificial crab, kamaboko (fish cakes), and fish sausages. Previously, studies from our laboratory and others showed that fish proteins from Alaska pollock, tuna, and tuna dark muscle, ameliorate hypercholesterolemia and nonalcoholic fatty liver disease (Hosomi et al., 2015, 2017; Maeda et al., 2017) and prevent obesity, hypercholesterolemia, and hypertension (Drotningsvik et al., 2018; Oishi & Dohmoto, 2009; Yathisha, Bhat, Karunasagar, & Mamatha, 2019). In addition, cod protein reduced fasting and postprandial glucose levels and increased peripheral insulin sensitivity compared to casein, in rats fed a high鈥恠ucrose diet (Lavigne, Marette, & Jacques, 2000).…”
Section: Introductionmentioning
confidence: 96%